Analysis of Determinants Driving Interest Student Accountancy for Role in World Businessman - Saputra, Rendra Bagus; Kurniawati, Lintang (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Commencing a firm or engaging in entrepreneurship is a means for individuals to generate income, so bolstering a nation's economy and employment opportunities. This study sought to examine the influence of motivation, environment, social media, digital marketing, and love of money on entrepreneurial inclinations. 973 alumni graduated in the years 2020 and 2021. This study employed a qualitative research approach, gathering data through a questionnaire administered via Google Forms. The data were examined using the purposive sampling technique based on the Slobin formula. The influence of motivation on the entrepreneurial aspirations of students is significant. The environment plays a significant role in shaping the amount of interest in entrepreneurship. Social media has a significant impact on the entrepreneurial aspirations of students. Digital marketing has a big impact on students' entrepreneurial interests. An individual's level of interest in entrepreneurship can be greatly influenced by their strong desire for riches.